The coloniality of biometric power: global digital empire, biometric state and the control of digital subjects in Nigeria - Iwuoha, Victor; Doevenspeck, Martin (Review of African Political Economy, 2025)
Countries in the global South are engaging and building strong relationships with powerful global organisations and big tech corporations, based on a profitable digital cooperation. This article explains this emerging trend using the concept of biometric coloniality of power, to show how techno-capitalist biometric identification interventions in the new biometric states in the global South replicate colonial relations of dominance. It draws on Nigeria’s experience to illustrate the utilisation of social hierarchies and biometric categories in the state-sponsored exclusion and disempowerment of the most vulnerable groups. The article argues that the rise of biometric states is associated with the political instrumentalisation of personal data, resulting in social conflict. Digital subjects confront and negotiate a deeply imbricated biometric power structure through which biometric policing, fraud, exclusion, surveillance, the breach of personal data privacy and other concrete materialisations of biometric authoritarianism are institutionalised. The article concludes that biometric states are complicit in multinational corporations’ monopolistic siege of Africa’s digital market, which allows for the unrestricted capture of digital data through ongoing digital commodification and dispossession.